Detection performance with many antennas available for bandwidth efficient uplink transmission in MU-MIMO systems - Torres, Paulo (2016)
This paper is concerned with Single Carrier (SC)/Frequency Domain Equalization (FDE) for bandwidthefﬁcient uplink block transmission, with Quadrature Amplitude Modulation (QAM) schemes, in a Multi-User (MU) Multi-Input Multi-Output (MIMO) system. The number of Base Station (BS) receiver antennas is assumed to be large, but not necessarily much larger than the overall number of transmitter antennas jointly using the same time/frequency resource at Mobile Terminals (MT). In this context, we consider several detection techniques and evaluate, in detail, the corresponding detection performances (discussed with the help of selected performance bounds), for a range of values regarding the number of available BS receiver antennas. From our performance results, we conclude that simple linear detection techniques, designed to avoid the need of complex matrix inversions, can lead to unacceptably high error ﬂoor levels. However, by combining the use of such simple linear detectors with an appropriate interference cancellation procedure - within an iterative Decision-Feedback (DF) technique -, a close approximation to the Single-Input Multi-Output (SIMO) Matched-Filter Bound (MFB) performance can be achieved after a few iterations, even for 64-QAM schemes, when the number of BS antennas is, at least, ﬁve times higher than the number of antennas which are jointly used at the user terminals.